Os Papéis das Organizações Sindicais e a Formação das Políticas Públicas para o Meio Rural: Estudo de Caso em um Município Mineiro - Carla Toledo (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2014)
This article aims to discuss a few issues related to the roles of two unions (of rural producers and of rural workers) in the dynamization of the rural world. It is a case study of a county of Minas Gerais, Brazil. This study is part of a Master of Science in Rural Extension research on the role of rural orga - nizations that nucleate producers and/or rural workers. Therefore, this paper presents the historical evolution of Brazilian public rural policies, outlining the changes of the unions’ performance after the Brazilian redemocratization, in the 1980’s. First, a bibliographic and documental review was held aiming to identify the roles of these organizations and the reasons why they have been created and their relationship with public policies. According to the research design, interviews were conducted with representatives from each organization studied, arguing how and whether these organizations – formed previously to the Brazilian redemocratization – manage to adapt themselves to the new roles assigned to them. There are evidences of a strong assistentialist role of these organizations, which ends up undermining their own political role as representatives.